The impact of two production task-mode types on FL vocabulary knowledge / Bahador Sadeghi - Sadeghi, Bahador (Universiti Teknologi MARA, Kedah, 2013)
In the ESL/EFL instructional context , the role of output tasks on target language learning has been investigated , and all of them have supported the positive role of output on target language acquisition, but few studies have compared the effect of two types of production modes ( written and oral output ) on target language acquisition, The present study examined the effects of two types of production modes on the productive English vocabulary knowledge .Two groups of intermediate learners (n=38) were subjected to the two production-modes tasks (Round Robin and Buzz group).Then T-test was used to analyze data. The Buzz group students better gained knowledge of vocabulary in comparison to those in the Round Robin group although no significant difference was observed between the two. The results represented that two types of production task played positive roles in improving the productive vocabulary knowledge of the learners. As a result, applying output tasks could be recommended to the syllabus and text book designers and teachers.